Features of prosthetic of lower edentulous jaw with a complex clinical picture - Yu. . Parshin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The greatest difficulties arise in the treatment of patients with complete loss of teeth on the lower jaw. One of the rational methods of prosthetics of the lower edentulous jaw in patients is the use of implants to support a removable denture. However, using even a small number (2 - 4) of the implants, as recommended by many clinicians, is negatively perceived by patients of elderly and senile age, because of the invasiveness and cost, which leads to a failure of implantation and use of traditional methods of prosthetics. Therefore, reducing the invasiveness of the intervention on the lower edentulous jaw and the use of a single implant is relevant in a complex clinical picture in this category of patients.